Effect of Pyrolysis Temperature of Glass Packaging Plastic Mineral Water Waste on Alternative Fuel Production - Purwo Subekti; Heri Suripto; Riszki Hidayat (Aptek, 2023)
The aim of this research is to obtain information on the effect of pyrolysis temperature of plastic waste from mineral water glass packaging on the production of liquids that can be used as alternative fuels (BBA). The material used to obtain BBA is plastic waste from xx brand mineral water glass packaging, which is heated using a pyrolysis reactor at a temperature of 255 to 280 ⁰C for 3 hours. Through the pyrolysis process, 369 to 404 mL of BBA liquid is produced. Based on the results of production data analysis, differences in combustion temperatures affect the yield of BBA liquid, the higher the combustion temperature will increase the BBA production produced.